The Innovation and Creativity of Religious Moderation Learning Through Sociology Learning and Pancasila and Citizenship Education in Public Schools and Madrasas Gorontalo City - Israpil Israpil; Suardi Suardi (Universitas of Muhammadiyah Makassar, 2021)
This study aims to explore educators' ideas regarding learning materials and methods that integrate moderation insights by utilizing creative learning media carried out in public schools and madrasas. The value of moderation insight is urgent to be implemented for students, given the widespread dissemination of information through misleading online media, including intolerant religious messages. This study used a qualitative descriptive approach, with data collection conducted through interviews and FGDs. The results of the study show: (1) Educators are very creative in using learning media technology, including: zoom meeting applications, WhatsApp, Telegram, and E-learning. Platforms provided by Google (Google Classroom, Google Forms, Google Meet), Kingmaster, Filmmora, Font Art, Camtasia, Quizizz, Microsoft 365, and create innovative learning modules. (2) Materials containing the value of religious moderation are found and integrated in various subjects, including Pancasila and Citizenship Education Lessons. The effectiveness of the use of learning media through the media has a significant impact on students' attitudes and experience improvement, as well as seriousness in participating in learning boldly. Penelitian ini bertujuan untuk mendeskripsikan dan menggali gagasan pendidik terkait materi dan metode pembelajaran yang mengintegrasikan wawasan moderasi beragama dengan memanfaatkan media pembelajaran secara kreatif yang dilaksanakan di sekolah umum dan madrasah. Nilai wawasan moderasi beragama urgen untuk diimplementasikan kepada peserta didik, mengingat maraknya penyebaran informasi melalui media online yang menyesatkan, termasuk pesan-pesan keagamaan yang intoleran. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan pengumpulan datanya dilakukan melalui wawancara dan FGD. Hasil penelitian menunjukkan: (1) Kalangan pendidik sangat kreatif menggunakan teknologi media pembelajaran, meliputi: aplikasi zoom meeting, WhatsApp, Telegram, dan E-learning. Platform yang disediakan oleh Google (Google Classroom, Google Forms, Google Meet), Kingmaster, Filmora, Font Art, Camtasia, Quizizz, Microsoft 365, dan membuat modul pembelajaran yang inovatif. (2) Materi yang mengandung nilai moderasi beragama ditemukan dan diintegrasikan dalam berbagai mata pelajaran antara lain mata pelajaran sosiologi dan Pelajaran Pendidikan Pancasila dan Kewarganegaraan. Efektivitas penggunaan media pembelajaran melalui media kreatif berdampak secara signifikan terhadap sikap peserta didik dan peningkatan kehadiran, serta keseriusan dalam mengikuti pembelajaran secara daring.